"Zamień moją żałobę w taniec". O narracji filmowej Wima Wendersa - Okupnik, Małgorzata (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2012)
Pina, a fi lm (2011) directed by Wim Wenders, falls outside any simple genre classifi cation. It may be treated as a documentary only, but it can also be regarded as an artistic fi lm because it talks about artists – dancers from the Tanztheater in Wuppertal (Germany) and their choreographies. Wenders uses artistic means of expression in the montage of scenes and particular takes. A three-dimensional technique allows him to enter the world of dance and show its beauty as well as the physicality of dancers. Wenders ncludes four Pina Bausch’s choreographies in the fi lm: Frühlingsopfer, Café Müller, Kontakthof,and Vollmond. The main themes of the fi lm are death, loss and loneliness, which also appear in all Pina Bausch’s choreographies. Work on the fi lm was a kind of “going through mourning”, both for the director and the dancers.